Incorporating a water-logging routine into CERES-Maize, and some preliminary evaluations - Toit, A.S. du; Prinsloo, M.A.; Wafula, B.M.; Thornton, Philip K. (African Journals Online, 2002)
The inability of CERES-Maize v3.0 to simulate a fluctuating water table has been identified as a major constraint in using this particular model in South Africa and in Kenya. Information regarding fluctuating water tables under specific conditions, and their influence on maize production, has been presented in South African literature. The objective of this study was to construct a simple water-logging subroutine based on these mechanisms, using the existing input data structure of CERES-Maize. Results indicate that it is possible to stimulate the impact of water logging on maize plants in this way. Further studies are needed to evaluate the assumptions made in this study and, if necessary, to make some refinements to the water-logging subroutine.